RANCANG BANGUN PROTOTYPE TURBIN VORTEX UNTUK PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) - Pudja Dianda Mayapada, Gede; Jasa, Lie; Suartika, I Made (Jurnal SPEKTRUM, 2022)
MHPP is a run of river hydroelectric power plant type, that does not require a large dam or water discharge, but rather diverts the flow rate of water into a channel. Vortex turbine utilizes whirlpool of water obtained from the spiral basin shape to push the turbine to rotate. The reason of this research was to decide the design of the MHPP prototype using a vortex turbine. This prototype is a miniature or laboratory scale. This research is designed to model the MHPP prototype using a Vortex turbine which is helpful for learning before it is implemented directly to the river. In this study, the prototype MHPP with vortex turbine was designed with a 0.3 m head, 1.5 dim input pipe, 4.5 L/s water flow, basin with an upper diameter of 40 cm, 40 cm height and 12 cm outlet and 41° cone angle. The runner blade design has 9 blades with a runner outer diameter of 15 cm, 5 cm neck diameter, and 5 cm runner width. This prototype is able to generate power of 0.387 Watt and has an efficiency of 2.93%.